(U–Th)/He chronology of the Robe River channel iron deposits, Hamersley Province, Western Australia - Danisik, M.; Evans, Noreen; Ramanaidou, E.R.; McDonald, Bradley; Mayers, C.; McInnes, Brent (Elsevier Science BV, 2013)
Channel iron deposits (CID) supply 40% of Australia's iron ore but their genesis is still the subject of debate. Two well-characterised samples of goethite/hematite CID from a diamond drill core in Mesa J of the Robe River area in Western Australia were dated using (U–Th)/He methods in order to constrain the timing of iron oxide formation and thereby provide a temporal context for CID genesis. (U–Th)/He ages (He ages) range from 25.7 ± 0.6 to 7.0 ± 0.8 Ma and, despite a high degree of scatter, they corroborate relationships expected from the internal ooidal stratigraphy. For individual ooids, the hematitic core is older than or indistinguishable from the age of the surrounding goethitic cortex. The goethitic cortices are, in turn, older than the ferruginised wood fragments recovered from the cementing goethitic matrix.The data suggest the following paragenesis: (i) Hematitic cores in ooids formed in the Early to Middle Miocene as documented by ages of ~ 14.3 ± 3.7 Ma and 18.3 ± 3.5 Ma measured in the shallower (8.2 m deep) and deeper (32.8 m) sample, respectively; (ii) Goethitic cortices of both samples formed in the late Middle to early Late Miocene at 11.6 ± 3.0 Ma; (iii) Wood fragments form a prominent component of the matrix and were ferruginised during the Late Miocene (He ages ranging from 9.4 ± 0.5 to 8.2 ± 0.4 Ma in the deeper core and 8.4 ± 0.9 to 7.0 ± 0.8 Ma in the shallower core). The data suggest that the unique environmental conditions conducive to CID formation existed during the Miocene and that a “typical Robe River CID sequence” likely took 4 to 8 Myr to accumulate.A methodological implication of this study is that it confirms the previous observation of Vasconcelos et al. (2013) suggesting that the temperature utilised for He-extraction from iron oxides has a critical impact on the mobility of parent nuclides. The typical ~ 1000 °C laser heating used for crystalline minerals like apatite or zircon induces loss of U and Th and results in erroneously old ages. Modest extraction temperature (< 500 °C), utilising a low-power laser or, preferably, a temperature-controllable resistance furnace is recommended.